Linguistic Strategies for Communicating Climate Change Information to Farmers in Imo State, Nigeria - Nwulu, F.N.; Onuegwunwoke, C.A; Amadi, G.U; Anuonye, F.D; Nzeakor, N.C; Obinna, V.O; Chukwu, K.U; Okere, M.C; Emeka, D.N; Mbarah, G.O; et al. (The Bioscan, 2026)
Effective communication of information concerning climate change is not done anyhow before the farm people. It uses sound deliberate linguistic strategies to reach the rural dwellers. This paper attempts to examine the linguistic strategy in place for the communication of climate change information to farmers. It examines features of climate change, climate change information needs of farmers; perceived benefits of climate change information; linguistic barriers for climate change information communication; and the linguistic strategy for communication. Multi-stage sampling technique was used in random selection of a total of 120 farmers. Data were using questionnaire and oral interview. Data obtained was analyzed using mean, percentages and standard deviation. Results showed that the respondents are aware of the following climate changes; changes in rainfall patterns (94.3%), rising temperature (97.5%), soil degradation (94.1%) and others. They need climate information such as weather and seasonal forecast (9.3%), early morning information (96.6%), market/economic information (99.1%). The benefits of using climate information include; promotion of better farm planning (M=2.48), increase productivity/yield (M=22.5), improved income (M=2.54), among others. The linguistic barriers include; use of complex scientific terminology (M=3.08), lack of translation into local language (M=3.13), low English language proficiency (M=3.17), among other barriers. The linguistic strategy include use of clear and simple language (M=2.41), use of audience centered language (M=2.54), use of metaphors/analogues (M=2.48), storytelling /narrations (M=2.57), framing and reframing languages (M=2.55).